Asuhan Kebidanan Pada Ibu Bersalin Dengan Tatalaksana Pijat Endorphin Dalam Membantu Mengurangi Intensitas Nyeri Dalam Persalinan Di Praktik Mandiri Bidan Husnel Hayati Wilayah Kerja Puskesmas Salo - Junia, Junia; Nislawaty, Nislawaty (Evidence Midwifery Journal, 2024)
The main problem that birthing patients can complain abouot and the active phase 1st stage card is pain in the birthing mother which can cause various pain problems that arise causing the mother to feel stressed and axcesisively worried. The aim of the rearch is to provide midwifery care to mother giving birth with labor pain at PMB Husnel Hayati. In the working area of the Salo community health center of June 2024. The results of the case study research given to Mrs. K with one visit or 1 day research at PMB Husnel Hayati, namely providing education first to the mother about labor pain and also providing care in the form of action by doing endhorphine massage on the mother in facing labor to relax the mother and transition the labor pain felt by the mother. The conclusion is that the care provided is carried out well and produces positive results. It is hoped that the subject and the community can increase knowledge about pain in labor and management of pain in labor.